2009
DOI: 10.1007/978-3-540-88789-8_9
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Properties of Nanoparticles Formed by Ion Implantation

Abstract: Abstract. This chapter broadly describes the formation, basic microstructure, and fundamental optoelectronic properties of nanocomposites synthesized by ion implantation. It is not meant as a complete literature survey and by no means includes all references on a subject that has seen a considerable amount of research effort in the past 15 years. However, it should be a good starting point for those new to the field and in a concise way summarize the main lines of research by discussing the optical, magnetic, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 87 publications
(113 reference statements)
0
13
0
1
Order By: Relevance
“…The local heating leads to the motion of the particles, i.e., Brownian motion occur as a result of the ther-modynamic process (Schachoff et al, 2015). The electronic energy loss induces the nucleation by radiolysis process and these nucle-ated particles grow and precipitates in the superficial implanted layer (Meldrum, Lopez, Magruder, Boatner, & White, 2010). Formation of micro structures might be due to the void nucleation mechanism.…”
Section: Results and Discussion 31 Scanning Electron Microscopymentioning
confidence: 99%
“…The local heating leads to the motion of the particles, i.e., Brownian motion occur as a result of the ther-modynamic process (Schachoff et al, 2015). The electronic energy loss induces the nucleation by radiolysis process and these nucle-ated particles grow and precipitates in the superficial implanted layer (Meldrum, Lopez, Magruder, Boatner, & White, 2010). Formation of micro structures might be due to the void nucleation mechanism.…”
Section: Results and Discussion 31 Scanning Electron Microscopymentioning
confidence: 99%
“…1͒, usually described by classical thermodynamic concepts discussed elsewhere. [7][8][9][10] Upon aging, two sets of structures are formed. The first set consists of TEM observable particles ͓Fig.…”
Section: Figmentioning
confidence: 99%
“…Their growth follows a nonhomogeneous coarsening process which produces both size and depth dispersed NP systems. [7][8][9][10] We have previously demonstrated that the classical nucleation route observed for most metal atoms implanted into silica films can be avoided in the case of Sn. 11 It was argued that, during a low temperature long-term thermal treatment ͑aging͒, there is formation of small atomic clusters with high thermal stability.…”
Section: Introductionmentioning
confidence: 99%
“…The metallic as well as semiconductor NCs exhibit enhanced optical properties [23]. These optical properties are due to the quantum effects as well as electronic properties influenced by the implanted ion species.…”
Section: Introductionmentioning
confidence: 99%
“…Larger NCs are primarily responsible for light absorption and scattering, whereas the smaller NCs are responsible for the nonlinear optical properties. The modified Mie expression [23] in Eq. 1 shows the absorption of light due to the size and ion species of NCs:…”
Section: Introductionmentioning
confidence: 99%